Wasaṭiyyah (moderation) as the principle and objective of the Shariah as a solution for preventing violence and extremism = Wasatiyyah (kesederhanaan) sebagai satu prinsip dan objektif Shariah adalah satu solusi mencegah keganasan dan ekstrim - Ali, Muhammad Mumtaz; Rafeeq, Muneer Muhammed (IIUM Press, International Islamic University Malaysia, 2018)
The Shariah, the foundation of the scheme of life, seems to be the most misunderstood concept of our time. The Shariah is confined to the domain of law in a rigid way and used out of context in an exclusivist manner. This has generated numerous implications to thought and life. It is generally assumed that the violent extremism that we witness in many parts of the world is the result of this misrepresentation of the Shariah. The situation demands a textual and contextual reading of the Shariah’s principles scientifically, especially, the principle of the wasatiyyah as an objective of the Shariah [Maqasid Shariah]. A correct view of the Shariah and the principle of wasatiyyah will help to remove the misunderstandings. It will also help to prevent the violent extremist and terrorist tendencies. This paper, therefore, aims at examining the principle of wasatiyyah based on the textual study of the Principle Sources – the Quran and Sunnah - and determines its scope to counter violence, extremism and terrorism. The socio-ethical dimensions and the principle of wasatiyyah as principles and objectives of the Shariah in relation to extremist trends will be explored and analyzed in this paper. This paper will present the principle of wasaṭiyyah as a solution for preventing the current extremist tendencies among some Muslims. The descriptive and analytical approaches will be employed in this study. Based on the textual study in a changing context, this paper concludes that the principle of wasaṭiyyah, owing its significance in the Sharī‘ah, needs to be highlighted and acknowledged as a major principle and objective of the Sharī‘ah which would be helpful to solve the societal problems besides its significance in private life. ********************************************************* Shariah yang merupakan asas kehidupan manusia adalah konsep yang seringkali disalah ertikan masa kini, Shariah yang dianggap terhad kepada undang-undang dan digunakan di luar konteks deengan cara ekslusif telah memberi pelbagai implikasi terhadap pemikiran dan kehidupan manusia. Secara amnya, keganasan golongan ekstrimis di beberapa Negara di dunia ini adalah berpunca daripada pemahaman Shariah yang salah. Situasi ini perlu kepada pembacaan prinsip-prinsip Shariah secara saintifik terhadap teks dan konteks terutamanya prinsip wasatiyyah sebagai satu bentuk objektif Shariah. Pandangan sebenar terhadap Shariah dan prinsip wasatiyyah dapat menghapuskan tanggapan yang salah dan mampu mencegah keganasan golongan ekstrimis dan terroris. Oleh itu makalah ini mengkaji prinsip wasatiyyah berdasarkan teks al-Quran dan Sunnah untuk mengenalpasti skopnya demi mencegah keganasan, ekstrimis dan terroris. Dimensi sosio-etika dan prinsip wasatiyyah sebagai objektif Shariah akan dianalisis dalam makalah ini. Makalah ini akan membincangkan prinsip wasaṭiyyah sebagai penyelesaian untuk mencegah kecenderungan ekstremis semasa di kalangan umat Islam. Pendekatan deskriptif dan analisis digunakan dalam kajian ini. Berdasarkan kajian tekstual makalah ini menyimpulkan bahawa prinsip wasaṭiyyah, perlu diakui sebagai objektif dan prinsip utama Sharī'ah yang akan membantu menyelesaikan masalah sosial selain kepentingannya dalam kehidupan setiap individu.